Desarrollo de instrumentación y prácticas para los laboratorios de fisiología I, II, III y equipos de diagnóstico y terapia - Corona Chávez, Farah Irene; Martínez Alarcón, Jorge Andrés (Revista Mexicana de Ingenieria Biomedica, 2002)
This project develops the necessary instrumentation to develop practical laboratory work for the course subjects of Physiology I, II, III, and Diagnostic and Therapy Equipment in a Biomedical Engineering program. We developed 3 principal systems: a virtual polygraph, a peristaltic bomb and 2 signal conditioning modules for pressure sensors. With this equipment, we designed 3 practical work sessions that are suitable for the mentioned courses, plus the equipment can be the basis for future practical work design.